The EBV-Encoded Oncoprotein, LMP1, Recruits and Transforms Fibroblasts via an ERK-MAPK-Dependent Mechanism - Alexandra M Davis; Abigail Rapley; Christopher W Dawson; Lawrence S Young; Mhairi A Morris (Pathogens, 2021)
Latent membrane protein 1 (LMP1), the major oncoprotein encoded by Epstein–Barr virus (EBV), is expressed at widely variable levels in undifferentiated nasopharyngeal carcinoma (NPC) biopsies, fueling intense debate in the field as to the importance of this oncogenic protein in disease pathogenesis. LMP1-positive NPCs are reportedly more aggressive, and in a similar vein, the presence of cancer-associated fibroblasts (CAFs) surrounding “nests” of tumour cells in NPC serve as indicators of poor prognosis. However, there is currently no evidence linking LMP1 expression and the presence of CAFs in NPC. In this study, we demonstrate the ability of LMP1 to recruit fibroblasts in vitro in an ERK-MAPK-dependent mechanism, along with enhanced viability, invasiveness and transformation to a myofibroblast-like phenotype. Taken together, these findings support a putative role for LMP1 in recruiting CAFs to the tumour microenvironment in NPC, ultimately contributing to metastatic disease.